Carbon and Oxygen Atoms Distribution along Low-Temperature Plasma Torch in the Magnetic Field - Myshkin (Mishkin) V. F. Vyacheslav Fedorovich; Izhoykin D. A. Dmitry Aleksandrovich; Bespala E. V. Evgeniy (Evgeny) Vladimirovich; Ushakov I. A. Ivan Alekseevich (Plasma, Microwave, Ion, Electron and Isotope Technologies, 2015)
Title screen